2020
DOI: 10.1002/smll.201906780
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanoassemblies: Tentacles Beat Satellites for Boosting Broadband NIR Plasmon Coupling Providing a Novel Candidate for SERS and Photothermal Therapy

Abstract: Optical theranostic applications demand near‐infrared (NIR) localized surface plasmon resonance (LSPR) and maximized electric field at nanosurfaces and nanojunctions, aiding diagnosis via Raman or optoacoustic imaging, and photothermal‐based therapies. To this end, multiple permutations and combinations of plasmonic nanostructures and molecular “glues” or linkers are employed to obtain nanoassemblies, such as nanobranches and core–satellite morphologies. An advanced nanoassembly morphology comprising multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Many different gold nanostructures are now available commercially, conrming the scalability of reproducible production. The ease of surface modication by functionalization with tags, 14,26,71,91 silica, 15 polymers, 92,93 DNA 67,94 or liposomes 95 has been a favourable factor for its use. Additionally, a coating of graphene oxide or silica onto gold nanostructures, 96,97 as well as incorporation of copper selenide (Cu-Se) into gold nanostructures 98,99 have been employed to boost the absorption cross-section and tune the LSPR into the NIR.…”
Section: Key Design Considerations Of Gold Nanostructure Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different gold nanostructures are now available commercially, conrming the scalability of reproducible production. The ease of surface modication by functionalization with tags, 14,26,71,91 silica, 15 polymers, 92,93 DNA 67,94 or liposomes 95 has been a favourable factor for its use. Additionally, a coating of graphene oxide or silica onto gold nanostructures, 96,97 as well as incorporation of copper selenide (Cu-Se) into gold nanostructures 98,99 have been employed to boost the absorption cross-section and tune the LSPR into the NIR.…”
Section: Key Design Considerations Of Gold Nanostructure Contrast Agentsmentioning
confidence: 99%
“…Such core-satellite morphologies have been reported using branched polymeric linkers with spherical core, 103 with DNA linkers utilizing gold nanorods as the core, 72,104 as well as with more complicated structures of caged gold nanorods as core. 105 Recently, Dey et al 91 have reported a distinct morphology of core multi-tentacle assemblies that provides the unique features of both core-satellites and branched nanochains. Such nano-assemblies feature an intense broadband absorbance extending throughout NIR I and exhibit dramatically improved NIR absorbance than that of core-satellite nanoassemblies.…”
Section: Key Design Considerations Of Gold Nanostructure Contrast Agentsmentioning
confidence: 99%
“…Plasmonic nanostructures featuring control over their morphology and tunable optical properties, especially tunable localized surface plasmon resonance (LSPR) and surface-enhanced Raman scattering (SERS), are of interest to nanomaterial scientists [1][2][3][4]. The coupled LSPR mode appears when plasmonic nanoparticles (NPs) are close to each other, resulting in coupling of the individual plasmon oscillations via near-field interactions [5]. This coupling strongly impacts the electric field distribution around the nanostructure, especially at the NP-NP junctions, or "hot-spots".…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, fabrication of various plasmonic nanoassemblies has been attempted. Among them, core-satellite nanoassemblies [5,17] have a unique arrangement, providing significantly better hot-spot control than other assemblies, such as globular assemblies, nanochains, and nanobranches [18,19]. Linker molecules that mediate the formation of such nanoassemblies and control the hot-spots (density and position) are, thus, significant.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Noteworthy, photo-driven heat conversion nanomaterials are indispensable for photonic hyperthermia, which could convert the near-infrared (NIR) light energy to generate regional heat for inducing tumor apoptosis. [11][12][13][14] However, recent progress of photonic hyperthermia mainly focuses on the first near-infrared light (NIR-I, 750-1000 nm) biowindow. [15][16][17][18] Comparatively, the second NIR biowindow (NIR-II, 1000-1700 nm) exhibits intrinsic advantages including minimal laser scattering coefficient, low photon absorbance, deep tissue penetration, and high maximum permissible exposure (MPE).…”
mentioning
confidence: 99%